2022
DOI: 10.26881/oandhs-2022.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 8-hydroxy-2-deoxyguanosine activity, apoptosis, acetylcholinesterase and antioxidant enzyme activity in Capoeta umbla brain exposed to chlorpyrifos

Abstract: In this study, neurotoxic responses to exposure to chlorpyrifos (CPF) at different doses (55 and 110 µg l-1) and at different time intervals (24 and 96 h) were investigated in Siraz fish (Capoeta umbla) using 8-hydroxy 2-deoxyguanosine (8-OHdG) activity, caspase-3, acetylcholinesterase (AChE) and oxidative stress parameters [malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione reductase (GR)]. In this study, the LC50 value of CPF was determined for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The exposure to CYP in group 2 resulted in significant reductions in lysozyme, WBC, and T. Ig levels. Previous studies have shown that long-term exposure to pyrethroids weakens the immune system of fish (Ullah et al 2018;Yang et al 2021;Kirici 2022). However, significant enhancements were observed in levels of lysozyme, T. Ig, and WBC levels of group 3 and 4 treated with GT extract.…”
Section: Histopathological Immunohistochemical and Immunofluorescence...mentioning
confidence: 77%
“…The exposure to CYP in group 2 resulted in significant reductions in lysozyme, WBC, and T. Ig levels. Previous studies have shown that long-term exposure to pyrethroids weakens the immune system of fish (Ullah et al 2018;Yang et al 2021;Kirici 2022). However, significant enhancements were observed in levels of lysozyme, T. Ig, and WBC levels of group 3 and 4 treated with GT extract.…”
Section: Histopathological Immunohistochemical and Immunofluorescence...mentioning
confidence: 77%
“…The quantification of the 8-hydroxy-2-deoxyguanosine (8-OHdG) (Catalogue No. : 201-00-0041/SunRed) level in each fish’s brain tissue was performed utilising ELISA (enzyme-linked immunosorbent assay) kits in accordance with the instructions provided by the manufacturer, as specified by Kirici (2022) .…”
Section: Methodsmentioning
confidence: 99%